Familial Breast Cancer: Disease Related Gene Mutations and Screening Strategies for Chinese Population - Shen, Lu; Zhang, Shizhen; Wang, Kaiyue; Wang, Xiaochen (Frontiers in Oncology, 2021)
Background: About 5-10% of breast cancer (BC) have a heredity background, and this subset of patients are referred to as familial breast cancer (FBC). In this review, we will summarize the susceptibility genes and genetic syndromes associated with FBC, then discuss the FBC screening and high-risk patient consulting strategies for the Chinese population. Methods: We searched the PubMed database for related articles published from January 2000 to August 2021. Finally, 380 pieces of literature that address the genetic genes and genetic syndromes related to FBC were included and reviewed. Results: We listed 16 FBC-related genes and divided them into three types of high, medium, and low penetrance genes according to different relative risk ratios. In addition, 6 genetic syndromes are found to be associated with FBC. We then summarized the currently exited screening strategies for FBC and discuss the screening strategies for FBC high-risk populations based on the Chinese situations. Conclusion: There are multiple gene mutations and genetic disease syndromes that are closely related to FBC. The NCCN guidelines have recommended corresponding screening strategies for these genetic diseases. But such guidelines for the Chinese population are still lacking. For screening of high-risk groups in the Chinese population, genetic testing is recommended after genetic counseling.